LIGHTWEIGHT DESIGN OF STEERING KNUCKLE BASED ON COMPREHENSIVE SENSITIVITY - MA Jian; YE NanHai; WU Rong; DENG Xin; HE Yun; WANG Li (Jixie qiangdu)
In the process of designing lightweight of the steering knuckle,because of too many random variables and various factors,it is easy to result in poor optimization results. We consider the effect of the random parameter variable on stress and total volume and put forward the concept of comprehensive sensitivity. Through the dynamic simulation we get the steering knuckle bearing under three typical working conditions. By the finite element analysis,we obtain extreme load condition data and the initial static and reliability indicators. We use comprehensive sensitivity analysis theory to get the final design variables. Finally,we complete the lightweight design by establishing mathematical model. The results show that the lightweight design method based on comprehensive sensitivity can reduce steering knuckle weight and maintain good static and fatigue reliability effectively and can be applied in the engineering field.